Geospatial Assessment of the Occurrence of Flooding In Informal Settlements in Ilala Municipality, Tanzania (Tanzania Journal for Population studies and Development, 2024)
This article assesses the occurrence of flooding in informal settlements of Ilala Municipality using quantitative and qualitative approaches. Non-probability sampling technique was used to select participants for participatory mapping. Data collection was done through participatory mapping, remote sensing, document review, and field observation. The weighted sum tool in ArcGIS was used to combine flood factors layers and create flood-prone area maps. Participatory mapping was used to map flood depth before data was converted for map visualization. Results indicated that areas with high to very high risk of flooding are generally decreasing over time. From 1990–2000 areas with high risk of flooding covered 31.1% of the study area, decreasing to 21.1% from 2001–2010, while from 2011–2020 it covered 21.6%. However, flood depths increased over time. From 1990–2000 the highest flood depth was 5ft decreasing to 4ft between 2011–2020. Hence, people living in informal settlements are more vulnerable and mostly affected by floods because of disposing of solid wastes into the river valley, which blocks drainage systems, thereby causing overflow of water. Therefore, regulations guiding human development near the river valleys should be improved and unlawful activities in the river valley be discouraged. Again, storm water drainage systems should be protected and well managed as the levels of storm water have become very high over time. Waste collection contracts should be given to private companies which are flexible and able to use alternative means of accessing unplanned streets to easily collect wastes.